Inhibition potential of margolonone and isomargolonone against the dengue virus protease using molecular modeling approaches - Choudhir, Gourav; Iram, Faiza; Israil,; Shahid, Mohammad; Shamsi, Anas; Hassan, Md Imtaiyaz; Islam, Asimul (Frontiers in Bioinformatics, 2025)
BackgroundDengue is a mosquito-borne viral disease with no cure. Inhibiting key enzymes vital in replication could manage the dengue virus infection. This study investigated the potential of margolonone and isomargolonone from Azadirachta indica to inhibit dengue virus replication.MethodsThe 3D structure of margolonone and isomargolonone were obtained from the PubChem database. The drug-likeness properties of these molecules were performed using a Swiss-ADME server. The molecular docking and molecular dynamics simulation assessed binding affinity and interactions.ResultsThe drug-likeness of parameters showed that Margolonone and isoMargolonone showed zero violation of Lipinski rules. Docking simulations showed that both compounds bind to the active site of a critical enzyme (NS3 protease) essential for viral replication. Molecular dynamics simulations suggested that isomargolonone may bind more stably to NS3 than margolonone. Additionally, MMPBSA analysis showed that Margolonone does not show favorable binding energy.ConclusionThese findings warrant further investigation of isomargolonone as a potential anti-dengue drug. Further in-vitro and in-vivo evaluations need to be done before accepting it as drug molecules.